Effectiveness of narrative therapy on Reducing Divorce Tendency and Its Components in Women With Early Marriage - maryam ghodsi; Hosein ahmad Barabadi Barabadi; Ahmad Heydarnia Heydarnia (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2018)
The purpose of this study was to investigate the effects of narrative therapy on divorce tendency and its components. The research method is semi experimental with pretest-posttest design and control group. The statistical population of this study included all married women aged 15 to 19 years attending secondary school in Neishabour, in the academic year 2016-2017. The statistical sample of the study included 16 people who had a high score in the Rusbult-Johnson-Morrow Divorce Questionnaire (1986) and volunteered for attending the sessions and were randomly assigned to the experimental and control group. Then the narrative therapy approach was performed individually in 9 steps for the experimental group. Finally, the post-test was taken from both the experimental and control groups. Data were analyzed by multivariate analysis of variance analysis of differential scores. Findings show that narrative therapy has been effective in reducing the tendency toward divorce in the experimental group (p<0/05; F=92/641). The implementation of therapeutic narratives individually reduced the components of tendency to withdraw from relationship and neglect. It also increased the dimensions of expressing feelings and loyalty. According to research findings, this approach can be utilized not only to improve relationships but also to reduce divorce rates in the community.